Absorptive Proficiency Berbasis Islamic Social Capital Menuju Keunggulan Bersaing Berkelanjutan - Mubarok, Muhammad Husni; Martini, Tina (BISNIS, 2023)
This study aims to develop an absorptive proficiency model based on Islamic social capital toward the exploitability knowledge and sustainable competitive advantage. This study used a purposive sampling with 260 respondents from the fashion industry in Central Java, Indonesia. The analysis technique used a structural equation modeling with AMOS software. The findings of this research indicate an increase in absorptive proficiency which is carried out by increasing Islamic social networks and the quality of trust. The findings of this study indicate an increase in exploitation knowledge and sustainable competitive advantage which is carried out by increasing absorptive proficiency. Based on the findings of this research, suggestions are put forward to ensure a more productive sustainable competitive advantage through more effective knowledge exploitation.